Revisioning Women and Drug Use - Ettorre, E. author. aut Link
IX, 166 p.
Keywords: This 'landmark' text by one of the most respected researchers in drug use considers the issues surrounding the gendering of drug use, and within this looks critically at two approaches - the classical and postmodern. Ettorre examines the idea of a drug-using society and the implications this holds for social inequality and exclusion.